Labour market forecasting - Weber, Enzo; Zika, Gerd (Nürnberg, 2013)
"Using the example of short-term forecasts for German employment figures, the article at hand examines the question whether the use of disaggregated information increases the forecast accuracy of the aggregate. For this purpose, the out-of-sample forecasts for the aggregated employment forecast are compared to and contrasted with forecasts based on a vector-autoregressive model, which includes not only the aggregate but also the numbers of gainfully employed people at the industry level. The Clark/West test is used in the model comparison. It becomes evident that disaggregation significantly improves the employment forecast. Moreover, fluctuation- window tests help identify the phases during which disaggregation increases forecast accuracy to the strongest extent."